2019
DOI: 10.1088/1361-6595/ab0c6a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-surface interaction: dielectric and metallic targets and their influence on the electric field profile in a kHz AC-driven He plasma jet

Abstract: targets and their influence on the electric field profile in a kHz AC-driven He plasma jet. Plasma Sources Science and Technology, 28(4), [045003].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 79 publications
(154 reference statements)
10
52
0
Order By: Relevance
“…The same macroscopic behaviors reported in Norberg et al [27] have been observed and their effect on the electron properties have been reported, with electron density close to the target reaching three times higher values with a metallic target than a glass target. Other experimental and numerical works [12,39,51] have found the same tendencies as in Norberg et al [27], in terms of influence of the target on discharge velocity, radial spreading on the target and electric field in the front of propagation.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The same macroscopic behaviors reported in Norberg et al [27] have been observed and their effect on the electron properties have been reported, with electron density close to the target reaching three times higher values with a metallic target than a glass target. Other experimental and numerical works [12,39,51] have found the same tendencies as in Norberg et al [27], in terms of influence of the target on discharge velocity, radial spreading on the target and electric field in the front of propagation.…”
Section: Introductionsupporting
confidence: 71%
“…The interaction of jets with dielectric surfaces of different permittivities has been addressed in several experimental and numerical works [2,5,10,12,15,20,26,27,33,39,45,50,51,53]. In Norberg et al [27] it has been studied numerically in 2D the impact of He jets on dielectric and metallic grounded targets with a −15 kV voltage pulse.…”
Section: Introductionmentioning
confidence: 99%
“…A method called stark polarization spectroscopy is used to detect the electric field by using OES on a forbidden line of He(2 1 P–4 1 F) and the closest allowed line of He (2 1 P–4 1 D) at 492.19 nm. The method is well described in more recent publications . The electric field strength value can be determined from the distance between the allowed and the forbidden He line and is given by the formula: E(normalkVcm1)=(58.557+18.116ΔitalicλFA+3130.96ΔitalicλFA2+845.6normalΔλnormalFnormalA3)0.5,where Δ λ FA is the shift of the peak of the forbidden line from the allowed line.…”
Section: Resultsmentioning
confidence: 99%
“…The electric field profile between the nozzle and target over the He plasma jet generated with 30 kHz discharge with 2 kV voltage amplitude was measured in Ref. [9], using optical emission spectroscopy on a forbidden line of Helium (2 1 P4 1 F). The electric field E delivered by the streamer to the metal grounded electrode is shown to be higher than E for the glass target case.…”
Section: Introductionmentioning
confidence: 99%